Use of Continuous Positive Airway Pressure (CPAP) in an Infant with COVID-19 patients in a tertiary care center of Gandaki Pradesh, Nepal - Bastola, Ramchandra; Shrestha, Shree Krishna; Shakya, Pragya; Dahal, Anita (Journal of Karnali Academy of Health Sciences, 2021)
COVID-19 in infancy is a rare disease among all COVID-19 patients. Here we report a case of 2 months old male child who was brought by parents with the complain of fever and running nose for 2 days. He was being treated with antibiotics and antipyretics from local pharmacy without improvement and was admitted in hospital for intravenous antibiotics. On 5th day of admission baby developed grunting and respiratory distress so referred to tertiary center for possible covid-19 infection. Further investigations led to the positivity of COVID-19 in PCR test. He was treated with antibiotics, steroids and kept in CPAP during respiratory distress for 40 hours and then to high flow oxygen therapy via hood box. CPAP during respiratory distress responded to the treatment dramatically. COVID-19 infection among infant though rare, it is important to consider CPAP and oxygen therapy via hood box as an important treatment modality in COVID-19 patients.